(3VhGHW efM GdGFJeGf GdeUQai h OhQgG ai GdMO ef GdeNGWQ GdeUGMHI dYedjI efM GdGFJeGf (B: s (3OQGSI ebGQfI Hjf GdbGfhfjf GdeUQi h GdYQGbi (B/ s - (3eMeO YGeQ eMeOs; (3gGfi SQi GdOjfs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2019)
(3JfGhdfG ai gPG GdQSGdI ehVhY GdGFJeGf GdeUQai h eG jeKdg ef Ggejg HGdZg ai GdGbJUGO GdeMdi(B: (3h SdWfG GdVhA Ydi GdeNGWQ Gdi JJYQV dgG GdHfhc GKfGA eeGQSJgG dCYeGdgG h GTGQJ Gdi Gf GdNWQ gh ef UaGJ GdYed GdeUQai h gh LRA dG jJLRC efg(B: (3h Ef eYQaI Jdc GdeNGWQ jJWdH JMOjOgG HObI h eYQaI CSHGHgG h GdYhGed GdJi JRjO ef GMJeGdGJ MOhKgG h gh eG jSGYO EOGQI GdGFJeGf Ydi GdJMhW efgG h JLfH BKGQgG GdSdHjI(B: (3Ke nJWQbfG Gdi ebQQGJ dLfg HGRd h Gge GdeYGjjQ hGdeHGOF GdJj GQSJgG GHJOGkA HHGRd (B((3hGMO(B) (3h GfJgGkA HHGRd (B((3KdGKI(B): (3aJeJ GdGTGQI Gdi Gge GdCgOGa h GdEUdGMGJ GdJi hVYJgG GddLfI YHQ GJaGbjJgG GdKdGKI h GdETGQI Gdi ehWf Gdbhg h GdVYa ai Jdc GdGJaGbjGJ h Yed ebGQfg dJMOjO EjLGHjGJgG hSdHjGJgG(B: (3h QcRJ GdOQGSI Ydi GKQ VhGHW efM GdGFJeGf GdeUQai hab eYGjjQ GdHfc GdeQcRi ef efXhQ bGfhfi ebGQf Hjf GdbGfhfjf GdYQGbi h GdeUQi(B: (3hYf OhQgG ai GdQbGHI Ydi GdGFJeGf ef NdGd efGbTI eaghe GdQbGHI GdeUQajI h COhGJ GdHfc GdeQcRi ai GdQbGHIs
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdJLGQj (B2019.s
(3HHjdhLQGajG(B: (3UaMGJ (B376-393.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdJLGQjs; (3GdGFJeGf s; (3GdGFJeGf GdeUQais; (3GdGYJeGO GdeSJfOjs; (3eYGjjQ HGRds; (3GdeNGWQ s; (3VhGHW efM GdGFJeGf GdeUQajs; (3QbGHI GdHfc GdeUQaj Ydj GdGFJeGfs; (3NWGH GdVeGfs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs